Effect of the haptic 3D virtual reality dental training simulator on assessment of tooth preparation - Akitaka Hattori; Ken-ichi Tonami; Jun Tsuruta; Masayuki Hideshima; Yasuyuki Kimura; Hiroshi Nitta; Kouji Araki (Elsevier, 2022)
Background/purpose: The haptic 3D virtual reality dental training simulator has been drawn attention as a educational strategy in Covid-19 pandemic. The purpose of this study is to investigate the feature of the haptics simulator in comparison with a conventional mannequin simulator by analyzing the assessment of products prepared by dental students using these two kinds of simulator. Materials and methods: The subjects were 30 students in the sixth-year classes of the faculty of dentistry. Abutments for a full cast crown were prepared by each subject using two kinds of simulator; one is the haptics simulator and the other is a mannequin simulator. For the resulted products, occlusal surface form, margin design, surface smoothness, taper angle, total cut volume and overall impression were rated by 3 evaluators. Score differences between two simulators were statistically analyzed. Results: The kinds of simulator affected subject performance for margin design and total cut volume. The differences in cutting feeling between the simulators as well as variation of stereoscopic ability in subjects were considerable reasons. Evaluators' rating was affected by difference in simulators for occlusal surface form, total cut volume, and overall impression. This may have been due to variation of stereoscopic ability in evaluators. Conclusion: The unique characteristics of virtual reality, such as the simulated cutting sensation and the simulated three-dimensional images created by stereo viewers, affect operators' performance and evaluators' rating. It was suggested that educational programs need to be constructed taking account of the characteristics of virtual reality to make the best use of the haptics simulator.